Reduction of Vulnerability and Disasters: Intervention of Public Budgeting Program 068 and Reactive Management - Mateo Medina, José Luis (2023)
Public Budgeting Program 068 (PP068 by its Spanish initials) is part of the National System for Disaster Risk Management financial strategy and is linked to disaster risk management processes—among them, the processes of Reactive Management (GR by its Spanish initials). It enables articulated interventions between entities from the three government levels to reduce the vulnerability of the population and their means of living. The study determined the relationship between PP068 and GR based on the budget allocation for the products and actions aimed at the preparation, response and rehabilitation processes. This means that the variables have a cause and effect relationship; this is to say, a considerable budget allocation in PP068 helps to put the preparation and response procedures from reactive management into operation, resulting in value creation in municipality interventions as a benefit. A weakness to overcome that has been identified is the lack of articulation between planning and budgeting. There is inadequate budget planning for each PP068 product and activity oriented to GR. Municipality officials lack knowledge of PP068 and GR. Finally, the position of head of the Disaster Risk Management Office in municipalities experiences high turnover.